Impact of Voluntary Muscle Activation on Stretch Reflex Excitability in Individuals With Hemiparetic Stroke - Patterson, Jacqueline R.; Dewald, Julius P. A.; Drogos, Justin M.; Gurari, Netta (Frontiers in Neurology, 2022)
Objective: To characterize how, following a stretch-induced attenuation, volitional muscle activation impacts stretch reflex activity in individuals with stroke. Methods: A robotic device rotated the paretic elbow of individuals with hemiparetic stroke from 70° to 150°, and then back to 70° elbow flexion at an angular speed of 120°/s. This stretching sequence was repeated twenty times. Subsequently, participants volitionally activated their elbow musculature or rested. Finally, the stretching sequence was repeated another twenty times. The flexors’ stretch reflex activity was quantified as the net torque measured at 135°. Results: Data from fifteen participants indicated that the stretching sequence attenuated the flexion torque (p<0.001) and resting sustained the attenuation (p=1.000). Contrastingly, based on data from fourteen participants, voluntary muscle activation increased the flexion torque (p<0.001) to an initial pre-stretch torque magnitude (p=1.000). Conclusions: Stretch reflex attenuation induced by repeated fast stretches may be nullified when individuals post-stroke volitionally activate their muscles. In contrast, resting may enable a sustained reflex attenuation if the individual remains relaxed. Significance: Stretching is commonly implemented to reduce hyperactive stretch reflexes following a stroke. These findings suggest that stretch reflex accommodation arising from repeated fast stretching may be reversed once an individual volitionally moves their paretic arm.